CORAL RECRUITMENT ON REEF BALLTM MODULES AT THE BENETE BAY, SUMBAWA ISLAND, INDONESIA - Imam Bachtiar; Windy Prayoga (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Reef BallTM structure is a popular artificial reef module that has been invested in many countries. Publication on its efficacy in promoting coral recruitment however remains lack of study or publication. This present study was aimed to examine the pattern of coral recruitment on reef ball structure at the Benete Bay of Sumbawa Island, Indonesia. Thirty reef-balls (dome shape; 0.90 cm height, 1.20 cm diameter) were monitored after three years of deployment. The results of this study showed that nearly all coral colonies grew on the outer vertical surface and upper side of the reef balls. The recruit number varied a lot between 1-76 colonies per module. Most recruits were belonged to the Family Acroporidae, which contributed approximately 76 percent to the whole recruitment (640 colonies). Branching acroporiid was the most abundant colonies (55%). Pocilloporidae and Faviidae both contributed approximately nine percent to the total recruitment, while Poritidae contributed about three percent. Other coral families only had <1% contribution. The diameter of coral colonies which were growing on the reef balls varied between 5-290 mm. The number of recruit on the ball was very low at 10 meter depth (1-5 colonies per ball) that was likely to be affected by sedimentation. This study showed that reef ball module can be effectively used as a method in rehabilitating damaged coral reefs, and developing a proto-reef.